Analysis of The Implementation of Sustainable Food Agricultural Land Protection Policy in Musi Rawas District Using the Interpretive Structural Modeling Method - Indarwanto; Yuwana; Romeida, Atra; Senoaji, Gunggung; Reflis; Yuristia, Rahmi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This study focuses on analyzing the implementation of Musi Rawas Regency Regional Regulation Number 3 of 2018 concerning Sustainable Food Crop Land Protection (LP2B). In the study, interviews were conducted with informants related to the research aimed at developing a strategy for implementing Musi Rawas Regency Regional Regulation Number 3 of 2018, concerning the protection of sustainable food crop land in Musi Rawas Regency. The method used in this study is interpretive structural modelling (ISM). The ISM method is a modeling technique that can summarize expert opinions to provide specific opinions on the hierarchy of sub-elements according to each element contained in the system. The results obtained from this study indicate that the main obstacle is the lack of optimal socialization regarding sustainable food crop land protection policies to the community, and the need for increased farmer training to implement sustainable agricultural practices to protect food crop areas and land sustainably.